Pengembangan Sistem Informasi Perpustakaan Berbasis WEB di SDN Watukosek Kabupaten Pasuruan - Bachrul Ilmi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
The purpose of this study is to produce a web-based library information system, and produce operational guide of web-based library information system. Product web-based library information system which has been developed then validated by experts of information technology in web fields, practitioner (teacher) and practitioner (librarian). Products which have been validated next tested on 5th grade students of SDN Watukosek of the 36 children. Research results show the expert assessment of the information technology in web fields, practitioner teacher, librarian and practitioner gives criteria "Very Valid", while the results of field trials to the gives students the criteria of "Very Good", so that the web-based library information system fit for use.